Co-creative practice reconciling theory and practice in tertiary student documentary production. Issue 1 (2nd January 2023) - Wright-Brough, Freya; Hart, Phoebe; Maher, Sean; Cake, Susan
ABSTRACT: Accommodating theory and practice is a significant pedagogical challenge for screen programmes in higher education. Integrating theory and practice within the pedagogy of documentary screen production raises specific issues related to its ethical obligations and social change remit. Designing screen studies programmes that effectively support students to become critically aware and reflexive practitioners requires historical and theoretical knowledge to underpin and inform production skillsets [Wayne 2003. "Reflections on Pedagogy." Journal of Media Practice 4 (1): 55–61; de Jong 2006. "From 'Doing' to 'Knowing What You are Doing': Kolb's Learning Theory in Teaching Documentary Practice." Journal of Media Practice 7 (2): 151–158]. Prompted by the reaccreditation of our degree, this article critically reflects on the suite of practice and theory-based units that collectively strengthen student understanding and skillsets in factual screen storytelling. Mezirow' three forms of reflection are framed within Kreber and Cranton's scholarship of teaching model, to guide reflection on curriculum, pedagogy and three student documentaries as exemplars of aspirational learning outcomes. Our reflections identify how co-creative processes embedded in a spiral curriculum course structure supports opportunities for students to innovate fundamentals of praxis within a community of practice.